A Tale of Two Cities: Understanding Children's Cycling Behavior From the Socio-Ecological Perspective - Yesiltepe, Demet; Pepping, Rian; Ling, Fiona Chun Man; Tempest, Gavin; Mauw, Steven; Janssen, Mirka; Hettinga, Florentina (Frontiers in Public Health, 2022)
The childhood obesity epidemic presents serious social, economic and health consequences worldwide. For researchers and policy makers alike, cycling has been a promising focus for developing long-term physically active lifestyles in urban environments. For children, cycling promotes exercise engagement, active transport opportunities, motor skill development and social interaction. However, across European cities, there are considerable discrepancies in the uptake of cycling amongst children. To understand and promote children’s cycling behavior, it is crucial to consider the complex social, physical and policy environment, and their interrelationships. We adopt the socio-ecological model to better understand how children’s cycling behavior is shaped at interpersonal, organizational and community level embedded within city policies. We will review cycling policies of Amsterdam (Netherlands) and Newcastle (UK), where stark contrasts in children’s cycling participation can be observed. Cycling policies in Amsterdam have mainly contributed to comprehensive organizational level changes, for example, cycling infrastructure development within the city, and significant progress was made at the community level where cycling has become part of the ‘Dutch culture’. Hence, cycling is a more common transportation mode in Amsterdam than in Newcastle. In Newcastle, policies primarily focus on organizational or community level changes. Progress was accelerated in response to COVID-19. Similar challenges for both cities related to the urgency to support cycling uptake of for children with low socio-economic background or cultural differences. We propose a “shared (cycle-)path” for policy makers and researchers.Collaboration is crucial in producing multi-component interventions at a policy level that recognize individual, interpersonal, community and organizational factors.